Trinkwasserversorgung: Privat gleich teuer? - Tim Starke; Oliver Rottmann; Mario Hesse; Alexander Kratzmann; Christoph Mengs (Wirtschaftsdienst, 2018)
Nachdem seit den 1970er Jahren ein Trend zur Deregulierung und Privatisierung öffentlicher Unternehmen bestand, hat sich diese Tendenz in der jüngeren Vergangenheit wieder umgekehrt. Am Beispiel der deutschen Trinkwasserversorgung in den 100 größten deutschen Städten wird untersucht, wie die Gesellschafterstruktur die Preisentwicklung in regulierten Märkten beeinflusst. – – The article examines the relationship between the degree of private ownership and the price level in the German drinking water market. In addition to a compact overview of important characteristics of the German drinking water supply and the regulatory framework, the empirical study focuses on the 100 largest communities and is based on a multivariate OLS regression and a fixed effects analysis using annual data for 2009-15. The results do not conclusively indicate a rise in prices due to a higher degree of private ownership. For future surveys, it might be useful to include key economic figures of the respective water supply companies into the analysis.
Keywords: L50; R29; R53; 330